Needs Analysis for Designing English for Tourism Practitioners at Lantan Village Using Language-Based Responsibility Model - Sabila, Widani Silvie Tsal; Sujana, I Made; Saputra, Agus; Kamaludin (Journal of English Education Forum (JEEF), 2025)
This study discusses the English language needs of tourism practitioners in Lantan Village, Central Lombok. This study identified 16 tourism actors, including tour guides and traders, who had difficulty communicating effectively due to limited English language skills. The study was conducted in Lantan Village, Central Lombok using R&D approach. Data collection procedures included observation, interviews and documentation, while the instruments used consisted of observation sheets and interview sheets. The results of this study indicate that a syllabus was created for tourism practitioners in Lantan Village, utilizing the Language-Based Responsibility Model (LBRM), this study conducted a needs analysis to determine the essential language skills needed to interact with international visitors. The findings of the study highlighted the need for English language training that is tailored to the local cultural context, leading to the development of a relevant syllabus aimed at improving communication skills. Ultimately, this study emphasizes that improving English language skills is essential to improving service quality and enriching tourist experiences, thus contributing to the development of sustainable tourism in Lantan Village.